The South Asian bibliographer : a list of current publications compiled by the Library of Congress Office, New Delhi.. - Library of Congress (New Delhi ; Thousand Oaks: Sage Publications, 1998)
Records publications acquired from Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, Sri Lanka, and Tibetan titles issued in India, China, and elsewhere.
Keywords: South Asia